1997
DOI: 10.1523/jneurosci.17-14-05416.1997
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Distribution of Autophosphorylated Calcium/Calmodulin-Dependent Protein Kinase II after Tetanic Stimulation in the CA1 Area of the Hippocampus

Abstract: Autophosphorylation of calcium/calmodulin-dependent protein kinase II (CaMKII) at threonine-286 produces Ca 2ϩ -independent kinase activity and has been proposed to be involved in induction of long-term potentiation by tetanic stimulation in the hippocampus. We have used an immunocytochemical method to visualize and quantify the pattern of autophosphorylation of CaMKII in hippocampal slices after tetanization of the Schaffer collateral pathway. Thirty minutes after tetanic stimulation, autophosphorylated CaM k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
165
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(180 citation statements)
references
References 55 publications
13
165
1
1
Order By: Relevance
“…These changes may also possibly have led to an enhanced potentiation that occluded further tetanic LTP. Regardless of the mechanisms involved, this evidence stresses the potentially deleterious effect of excessive overexpression or overactivation of a protein which, in the case of CaMKII, is consistent with the fact that physiologically, only a small increase (15%) in CaMKII levels is triggered by LTP (Ouyang et al 1997). By extension, this confirms that complete or even partial downregulation of a gene may impose non-physiological conditions and engage nonspecific responses obscuring the expected effect.…”
Section: Transgenesis From the Test-tube To The Behaving Animalsupporting
confidence: 70%
See 1 more Smart Citation
“…These changes may also possibly have led to an enhanced potentiation that occluded further tetanic LTP. Regardless of the mechanisms involved, this evidence stresses the potentially deleterious effect of excessive overexpression or overactivation of a protein which, in the case of CaMKII, is consistent with the fact that physiologically, only a small increase (15%) in CaMKII levels is triggered by LTP (Ouyang et al 1997). By extension, this confirms that complete or even partial downregulation of a gene may impose non-physiological conditions and engage nonspecific responses obscuring the expected effect.…”
Section: Transgenesis From the Test-tube To The Behaving Animalsupporting
confidence: 70%
“…These brain structures are known to experience plastic changes upon stimulation (LTP, LTD) and to support some aspects of learning and memory. Further, after initial stimulation by calcium, CaMKII has the ability to maintain itself in an active state for long periods of time by autophosphorylation on threonine 286 (Hanson & Schulman 1992;Ouyang et al 1997), a process thought to leave a molecular trace of previous Ca 2 1 -induced activity. A counterpart to CaMKII is the protein phosphatase CN, the only known Ca 2 1 /calmodulindependent protein phosphatase in the brain.…”
Section: A Calcium-calmodulin Switchmentioning
confidence: 99%
“…The CaMK-related peptide and CaMK VI RNA were increased in the rat hippocampus by KA (Vreugdenhil et al, 1999). Although the exact functions of p-CaMK II in the hippocampus has not been well elucidated, several reports have demonstrated that the phosphorylation of CaMK II in the hippocampal region may play an important role in the regulation of neurotoxicity (Ouyang et al, 1997;Shamloo et al, 2000). Especially, our recent study has shown that KA administered i.c.v.…”
Section: Discussionmentioning
confidence: 93%
“…What mRNAs could be captured by tagged synapses? We do not have yet a definitive answer to this question, but inputspecific stimulation delivered to the apical dendrites has been shown to trigger the translation of microtubule associated protein 2 (MAP2) and CaMKII mRNAs localized in that dendritic compartment Ouyang et al, 1997;Ouyang et al, 1999;Steward and Halpain, 1999). Much effort has been also put on the identification of the mRNA cargo that travels to synapses (Kiebler and Bassell, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%